Kompleksitas Keamanan Kawasan dan Tantangan Kerja Sama Keamanan Asia Timur - Al Syahrin, M. Najeri (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2018)
This article will explain the regional security complex as a key challenge in the establishment of regional security cooperation in East Asia. The complex of security in East Asia described by explaining the security relations between North Korea and South Korea, China and Japan, the United States with Japan, and China with the United States and a pattern of chain reaction to the various security policies of these countries. This security complex makes it difficult to establish effective regional security cooperation. The Challenge of the regional security complex that most decisive in the formation of cooperation that will be done by the countries of the East Asia region is due to competition and differences of interests between the United States and China as a superpower state in the region. In addition, the many differences in the nature and orientation of political interests of Japan, South Korea, and North Korea are also still a constraint in the formation of regional security organizations and cooperation.